Incentive-Based Subsidies : Designing Output-Based Subsidies for Water Consumption - Gomez-Lobo, Andres (World Bank, Washington, DC, 2012)
To guarantee adequate and affordable water and sanitation services for vulnerable households, Chile introduced an individual means-tested water consumption subsidy a decade ago. Although the public authorities determine how the subsidy is applied, the mostly private companies deliver the service - under a scheme with built-in incentives to ensure cost-effective service delivery by the companies and low wastage by the customers. This case study reviews Chile's experience of using tax-funded subsidy payments, contingent on delivery of service by water companies. Funding the subsidy through general taxation allows the regulator to set tariffs according to economic criteria. Targeting allows scarce resources to be directed to those who need subsidies most. Both characteristics reduce the financial burden on the government as compared with the universal subsidy used in the past.